2019
DOI: 10.3390/app9235063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atmospheric Turbulence on OAM-POL-FDM Hybrid Multiplexing Communication System

Abstract: This paper proposes a 32-channel-hybrid-multiplexing system on atmospheric turbulence. With the utilization of the hybrid multiplexing of orbital angular momentum (OAM), polarization, and frequency, the communication speed of the system can be significantly improved, and this system can be well combined with the existing frequency division multiplexing (FDM) optical communication network. Within this communication system, we discuss the effects of different turbulence intensities on the phase, OAM crosstalk, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…This leads to aberration of the beam wavefront from random power and phase perturbations [65]. This results in the signal initially launched in a particular mode to spread to other modes [66]. The amount of spreading is influenced by the strength of the atmospheric turbulence.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to aberration of the beam wavefront from random power and phase perturbations [65]. This results in the signal initially launched in a particular mode to spread to other modes [66]. The amount of spreading is influenced by the strength of the atmospheric turbulence.…”
Section: Resultsmentioning
confidence: 99%
“…The application of OAM modes to realize high-speed FSO links has also been reported by different research groups [35][36][37][38][39]. The designing and evaluation of a low-density parity check coded FSO link incorporating high-capacity transmission under strong turbulence conditions using OAM multiplexing has been discussed by Z Qu.…”
Section: Introductionmentioning
confidence: 95%
“…L. Li et al reported an OAM-multiplexed FSO communication system, where 80-Gbps information is transmitted between two ground terminals separated at 100 m via an unmanned aerial vehicle (UAV) using two independent 40-Gbps QPSK-modulated OAM beams [38]. Z. Zhao et al reported an ultrahigh capacity FSO communication system over strong atmospheric turbulence conditions by incorporating hybridization of OAM multiplexing, polarization multiplexing, and frequency multiplexing [39]. The research works in references [40][41][42][43][44] report the simulative analysis of MDM-based high-capacity radio over fiber (RoF) links.…”
Section: Introductionmentioning
confidence: 99%
“…There are several technologies that can significantly improve the channel capacity in an FSO system, for instance, high-level modulation formats [4], wavelength division multiplexing [5], space division multiplexing [6], and angular momentum multiplexing [7]. However, the gap between the capacity of an FSO system and Shannon limit still exists.…”
Section: Introductionmentioning
confidence: 99%